Use of Leukocyte-and Platelet-Rich Fibrin for Bone Regeneration: A Systematic Review - Bastami, Farshid; Khojasteh, Arash (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Introduction: Leukocyte- and platelet- rich fibrin (L-PRF) is a fibrin matrix in which the platelet cytokines, growth factors and cells are trapped and this material has been recruited in reconstruction of various defects. The aim of this study was to systematically review of the published data on the effectiveness of using L-PRF on regeneration of bone defects in oral and maxillofacial surgeries. Materials and Methods: Medline and Cochrane Central databases were searched for related articles up to and including August 2015. Being English, having ≥ four weeks follow-up, and clinical, radiographic, histological and histomorphometric assessments were the inclusion criteria. Results: Twenty-four animal studies and 45 human trials were included that reported the rate of new bone formation (NBF). Also, 38 human reports with low levels of evidence to list evaluating various applications of L-PRF in oral and maxillofacial reconstructions were assessed. Using L-PRF either solely or mixed in human trials was evaluated and divided into six groups of sinus floor augmentation and guided bone regeneration (GBR) technique, socket preservation, periodontal intra-bony defects (PID) regeneration, peri-apical and endo-periodontal defects treatment, peri-implant bone regeneration and treatment of bisphosphonate-related osteonecrosis of the jaw (BRONJ). Moreover, other uses of L-PRF with bone regeneration purposes in oral and maxillofacial surgeries were discussed. Conclusion: As a consequence, although L-PRF either solely or mixed showed challengeable outcomes in animal studies, it was shown to be effective used to accelerate and enhance new bone formation in human studies. However, future clinical trials in some treatment areas are needed with larger sample sizes and long follow-ups to arrive at an evidence-based conclusion.